Self-Care Among Patients With Inflammatory Bowel Disease: An Interview Study - Lovén Wickman, Ulrica (Gastroenterol Nurs, 2016)
Inflammatory bowel disease (IBD) is a chronic disease of unknown etiology. The disease occurs early in life and the burden of symptoms is significant. Patients need to perform self-care to handle their symptoms, but knowledge about what kind of self-care patients do is limited and these individuals need to learn how to manage the symptoms that arise. The aim of this study was to explore self-care among patients with IBD. Twenty adult patients with IBD, 25–66 years of age, were interviewed. Data were analyzed by performing a qualitative content analysis. Four categories with 10 subcategories emerged from the analysis of the interviews. The self-care patients perform consists of symptom recognition (subcategories: physiological sensations and psychological sensations), handling of symptoms (subcategories: adapting the diet, using medical treatment, stress management, and using complementary alternative medicine), planning life (subcategories: planning for when to do activities and when to refrain from activities), and seeking new options (subcategories: seeking knowledge and personal contacts). Self-care consists of symptom recognition, handling life through planning, and accommodating the existing situation with the ultimate goal of maintaining well-being. Being one step ahead facilitates living with IBD. A decision to actively participate in care of a chronic illness is a prerequisite for self-care. Healthcare professionals must consider patients' potential for and desire for self-care when giving advice on self-care activities. Doing so may help people better cope with IBD.